A inflaç\~ao brasileira na década de 2000 e a importância de políticas n\~ao monetárias de controle - Julia de Medeiros Braga (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper presents estimates for Brazilian inflation during the 2000s. The results of a structural model with two endogenous variables - wage inflation and consumer inflation - indicate that: i) the demand indicator was not statistically significant in the consumer inflation, but it was important to explain wage inflation; ii) variations in the exchange rate and in commodity prices were the key determinants of consumer inflation. In contrast, disaggregated estimates for consumer goods and services indicated the role of wages as a determinant of variations in service prices which are not monitored by government. Wage impacts on final aggregate prices, however, were not strong due to the rise in productivity. Finally, the evidence reported for monitored prices suggests that non-monetary policies adopted in this decade, consisting of regulatory and fiscal measures, were effective in controlling inflation.
Keywords: E31; E64; 330; Inflation; Brasilien